Application of ultrasound in cardiovascular intervention via the distal radial artery approach: New wine in old bottles? - Chen, Tao; Yu, Xiaolong; Song, Ruixiao; Li, Lamei; Cai, Gaojun (Frontiers in Cardiovascular Medicine, 2022)
The distal radial artery (DRA) approach has emerged as a new approach in cardiovascular intervention. In recent years, ultrasound was widely used in the cardiovascualr intervention via the DRA approach.This article systematically discussed the progress of ultrasound in preoperative vascular assessment, intraoperative guided puncture and postoperative observation of complications via the DRA approach.